Energiaadó az Európai Unióban - energiaadózás és az Európa 2020 stratégia összefüggései - Lovas, Dóra (Közép-Európai Közlemények, 2017)
The issues related to the energy law came into my field of interest in 2005, when I made a news summary for the kozjavak.hu website (MTA-DE Public Service Research Group) about the Energy Union. Then I wrote an entry for the same website entitled “Energiaunió megszilárdításához vezető út” in April 2006. Currently, I am a PhD student at the Géza Marton Doctoral School of Legal Studies at the University of Debrecen and I deal with the Enery Union in the European integration. The purpose of my research is to call attention to the importance of the still evolving energy taxation in the EU regulation, and its potential effects on the goals of the Europe 2020 startegy related to the energy policy. The taxation of the energy sector in the EU member states began to give a unified image with the acceptance of the Senate 2003/96/EK principle, but the afterward problems are still unsolved. To mention some of these problems, the tax issue belongs to the Union members’ basic sovereign rights, so it is hard to make a decision in connection with it. Moreover, the topicality of my research is given by these outstanding problems, plus the fact that the attainment of the 2020 strategy’s goals in connection with the energy policy and climate change is influenced by the energy policy regulation. I analyze the union and domestic acts, as well as the legal documents through historical research in Law and law comparative methods considering the legislature aims and defining the possible consequences of the regulation, its negative and positive points. In conclusion, I suppose that the energy taxation and energy policy have more and more significant role in the European integration. The current union energy taxation is based on the Senate 2003/96/EK principle, but literature researchers and other investigations revealed the emerging problems after the acceptance of this law. This case is enlighten by the European Commission’s proposal regarding to the review of this guideline as well.